Conceptual design and evaluation of membrane gas separation-based CO2 recovery unit for CO2 electrolyzers employing anion exchange membranes - Lee, Hyunshin; Chung, Wonsuk; Roh, Kosan (Elsevier BV, 2024)
Anion exchange membrane (AEM)-based electrolysis for CO2 reduction reaction (CO2RR) has garnered attention as a promising carbon dioxide utilization technology due to its superior energy efficiency at high current densities. The major drawback of AEM-based electrolysis for CO2RR is CO2 crossover, which leads to the loss of introduced CO2 feedstock and thus detrimentally affects the process's overall economic and environmental viability. We design a 3-stage membrane-based CO2 recovery unit to capture CO2 from the mixture of CO2 and O-2 discharged from the anode side of AEM-based CO2 electrolyzers. The membrane area is optimized via a hybrid of genetic algorithm and 'fmincon' in MATLAB. The estimated CO2 capture cost ranges from 43.3 to 109.3 USD/tCO(2), which is economically comparable to piperazine-based amine scrubbing units when recovering CO2 at a purity of up to 99.5 mol.% under a CO2/O-2 molar ratio of 1.5 similar to 2. The carbon footprint of the designed process ranges from -0.936 to -0.838 tCO(2)eq/tCO(2)-captured, indicating superior environmental performance compared to those of the piperazine-based amine scrubbing units.